New training challenges in Information and Communication: micro-credentials - Sanz-Martos, Sandra (Anuario ThinkEPI, 2024)
Microcredentials are transforming higher education by offering modular and flexible training that meets the demands of the labor market. For schools of Information and Communication, they represent both an opportunity and a challenge: they must design dynamic programs, identify specific competencies, and establish closer connections with the professional world. Undoubtedly, this is a time for reflection to continue evolving and fostering lifelong learning.
Keywords: Microcredential; Professional competencies; Learning pathways; Dual education; Artificial intelligence; Lifelong learning